Polymer film and method for producing same, and laminate and method for producing same
The polymer film with a high volume content of liquid crystal polymer particles in the particle-containing layer addresses the issue of high dielectric loss tangents in existing films, resulting in reduced transmission losses for high-frequency communication devices.
Patent Information
- Application Number
- JP2021126191
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-07-30
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2041-07-30
AI Technical Summary
Existing polymer films used in high-frequency communication devices have high dielectric loss tangents, leading to increased transmission losses.
A polymer film with a particle-containing layer containing liquid crystal polymer particles, where the content of the liquid crystal polymer particles is 40% by volume or more, and the dielectric loss tangent of the liquid crystal polymer particles is smaller than that of the resin.
The polymer film achieves a significantly reduced dielectric loss tangent, thereby minimizing transmission losses in high-frequency communication devices.
Smart Images

Figure 0007667012000001
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a polymer film and a method for producing the same, and a laminate and a method for producing the same. [Background technology]
[0002] In recent years, the frequencies used in communication devices have tended to become very high. In order to suppress transmission loss in the high frequency band, there is a demand for insulating materials used in circuit boards to have low relative dielectric constants and dielectric loss tangents.
[0003] As a conventional liquid crystal polymer article, for example, a method described in Patent Document 1 is known. Patent document 1 describes a multiaxially reinforced liquid crystal polymer article comprising a polymer matrix and oriented particles embedded in the matrix, where the oriented particles comprise a first liquid crystal polymer and the matrix comprises a second liquid crystal polymer having a lower melting point than the first liquid crystal polymer. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 7-3124 Summary of the Invention [Problem to be solved by the invention]
[0005] An object of the present invention is to provide a polymer film having a small dielectric tangent and a method for producing the same. Another object of the present invention is to provide a laminate using the above polymer film and a method for producing the same. [Means for solving the problem]
[0006] Means for solving the above problems include the following aspects. <1> A polymer film having a particle-containing layer containing at least one resin selected from the group consisting of a liquid crystal polymer, a polysulfone resin, a polyethersulfone resin, and a polyphenylene sulfide resin, and liquid crystal polymer particles, wherein the content of the liquid crystal polymer particles in the particle-containing layer is 40 volume % or more. <2> The resin is a liquid crystal polymer. <1> The polymer film according to claim 1. <3> The solubility of the resin in N-methylpyrrolidone at 140°C is 1% by mass or more. <1> or <2> The polymer film according to claim 1. <4> The resin contains a liquid crystal polymer having a repeating unit represented by any one of the following formulas (1) to (3): <1> ~ <3> 13. The polymer film according to claim 12, Formula (1) -O-Ar 1 -CO- Formula (2) -CO-Ar 2 -CO- Formula (3) -X-Ar 3 -Y- In formulas (1) to (3), Ar 1 represents a phenylene group, a naphthylene group, or a biphenylylene group; Ar 2 and Ar 3 each independently represents a phenylene group, a naphthylene group, a biphenylylene group, or a group represented by the following formula (4), X and Y each independently represent an oxygen atom or an imino group, Ar 1 ~Ar 3 Each hydrogen atom in the above group represented by the formula: may be independently substituted with a halogen atom, an alkyl group or an aryl group. Formula (4) -Ar 4 -Z-Ar 5 - In formula (4), Ar 4 and Ar 5 each independently represents a phenylene group or a naphthylene group, and Z represents an oxygen atom, a sulfur atom, a carbonyl group, a sulfonyl group, or an alkylene group. <5> The liquid crystal polymer particles have a smaller dielectric tangent than the resin. <1> ~ <4> 13. The polymer film according to claim 12, <6> The liquid crystal polymer particles have a median diameter of 0.1 μm to 30 μm. <1> ~Claims 5. A polymer film according to any one of claims 1 to 4. <7> The liquid crystal polymer particles include liquid crystal polymer particles whose surfaces have been subjected to an oxidation treatment. <1> ~ <6> 13. The polymer film according to claim 12, <8> <1> ~ <7> 10. A laminate comprising the polymer film according to any one of claims 1 to 9 and a metal layer or metal wiring. <9> A resin layer is further provided between the polymer film and the metal layer or metal wiring. <8> The laminate according to claim 1. <10> The resin layer contains the resin in the particle-containing layer. <9> The laminate according to claim 1. <11> The average thickness of the resin layer is 5 μm or less. <9> or <10> The laminate according to claim 1. <12> A method for producing a polymer film, comprising: a forming step of forming a particle-containing layer on a substrate by applying to the substrate a polymer solution containing at least one resin selected from the group consisting of a liquid crystal polymer, a polysulfone resin, a polyethersulfone resin, and a polyphenylene sulfide resin, liquid crystal polymer particles, and an organic solvent, and drying the applied solution; and a heating step of heating the particle-containing layer at a temperature equal to or higher than the glass transition temperature of the resin, wherein the content of the liquid crystal polymer particles in the particle-containing layer after the heating step is 40 volume % or more. <13> A method for producing a laminate, comprising: a laminate-forming step of forming a laminate having a particle-containing layer on a substrate by applying to the substrate a polymer solution containing at least one resin selected from the group consisting of a liquid crystal polymer, a polysulfone resin, a polyethersulfone resin, and a polyphenylene sulfide resin, liquid crystal polymer particles, and an organic solvent, and drying the applied solution; and a heating step of heating the particle-containing layer at a temperature equal to or higher than the glass transition temperature of the resin, wherein the content of the liquid crystal polymer particles in the particle-containing layer after the heating step is 40 volume % or more. <14> The substrate has a metal layer or metal wiring. <13> A method for producing the laminate described in claim 1. <15> The surface roughness Rz of the surface of the metal layer or metal wiring on the particle-containing layer side is 1.0 μm or less. <14> A method for producing the laminate described in claim 1. <16> Further comprising a resin layer between the substrate and the particle-containing layer; <13> ~ <15> 13. A method for producing the laminate according to claim 12. <17> The resin layer contains the resin in the particle-containing layer. <13> ~ <16> 13. A method for producing the laminate according to claim 12. Effect of the Invention
[0007] According to an embodiment of the present invention, it is possible to provide a polymer film having a small dielectric tangent and a method for producing the same. According to another embodiment of the present invention, a laminate using the above polymer film and a method for producing the same can be provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] The contents of the present disclosure will be described in detail below. The following description of the components may be based on a representative embodiment of the present disclosure, but the present disclosure is not limited to such an embodiment. In this specification, the use of "to" indicating a numerical range means that the numerical values before and after it are included as the lower limit and upper limit. In the numerical ranges described in the present disclosure in stages, the upper or lower limit value described in one numerical range may be replaced with the upper or lower limit value of another numerical range described in stages. In addition, in the numerical ranges described in the present disclosure, the upper or lower limit value of the numerical range may be replaced with a value shown in the examples. In addition, in the description of groups (atomic groups) in this specification, descriptions that do not indicate whether they are substituted or unsubstituted include those that have no substituents as well as those that have a substituent. For example, an "alkyl group" includes not only an alkyl group that has no substituents (unsubstituted alkyl groups) but also an alkyl group that has a substituent (substituted alkyl groups). In this specification, "(meth)acrylic" is a term used as a concept including both acrylic and methacrylic, and "(meth)acryloyl" is a term used as a concept including both acryloyl and methacryloyl. In addition, the term "step" in this specification includes not only an independent step, but also a step that cannot be clearly distinguished from other steps, as long as the intended purpose of the step is achieved. In addition, in this disclosure, "mass %" and "weight %" are synonymous, and "parts by mass" and "parts by weight" are synonymous. Furthermore, in the present disclosure, combinations of two or more preferred embodiments are more preferred embodiments. In addition, unless otherwise specified, the weight average molecular weight (Mw) and number average molecular weight (Mn) in the present disclosure are molecular weights detected by a gel permeation chromatography (GPC) analyzer using a column of TSKgel SuperHM-H (product name of Tosoh Corporation) in a solvent of PFP (pentafluorophenol) / chloroform = 1 / 2 (mass ratio) and a differential refractometer, and converted using polystyrene as a standard substance.
[0009] (Polymer film) The polymer film according to the present disclosure has a particle-containing layer containing at least one resin selected from the group consisting of a liquid crystal polymer, a polysulfone resin, a polyethersulfone resin, and a polyphenylene sulfide resin, and liquid crystal polymer particles, and the content of the liquid crystal polymer particles in the particle-containing layer is 40 volume % or more.
[0010] As a result of extensive investigations, the present inventors have found that the above-mentioned structure makes it possible to provide a polymer film having a small dielectric loss tangent. Although the detailed mechanism by which the above effects are obtained is unclear, it is speculated as follows. The polymer film according to the present disclosure contains at least one resin selected from the group consisting of a liquid crystal polymer, a polysulfone resin, a polyethersulfone resin, and a polyphenylene sulfide resin, and liquid crystal polymer particles, and thus the liquid crystal polymer particles can be highly loaded in the particle-containing layer, and the highly loaded liquid crystal polymer particles can provide a polymer film with a small dielectric tangent.
[0011] <Particle-containing layer> The polymer film according to the present disclosure has a particle-containing layer, and the particle-containing layer contains at least one resin selected from the group consisting of a liquid crystal polymer, a polysulfone resin, a polyethersulfone resin, and a polyphenylene sulfide resin, and liquid crystal polymer particles. The content of the liquid crystal polymer particles in the particle-containing layer is 40% by volume or more.
[0012] <<Resin>> The particle-containing layer contains at least one resin selected from the group consisting of a liquid crystal polymer, a polysulfone resin, a polyethersulfone resin, and a polyphenylene sulfide resin, and liquid crystal polymer particles. From the viewpoint of the dielectric tangent of the film, a liquid crystal polymer is preferable, and from the viewpoints of heat resistance and mechanical strength, at least one resin selected from the group consisting of a polysulfone resin, a polyethersulfone resin, and a polyphenylene sulfide resin is preferable.
[0013] The weight average molecular weight Mw of the resin is preferably 1,000 or more, more preferably 2,000 or more, and particularly preferably 5,000 or more. The weight average molecular weight Mw of the resin is preferably 1,000,000 or less, more preferably 300,000 or less, and particularly preferably less than 100,000.
[0014] From the viewpoints of the dielectric tangent of the film, adhesion to the metal foil or metal wiring, and heat resistance, the glass transition temperature Tg of the above resin is preferably 150°C or higher, more preferably 200°C or higher, and particularly preferably 200°C or higher but lower than 280°C. The glass transition temperature Tg in this disclosure is measured using a differential scanning calorimetry (DSC) instrument.
[0015] The solubility of the above resin in N-methylpyrrolidone at 140°C is preferably 1 mass% or more, more preferably 2 mass% or more, even more preferably 3 mass% or more, and particularly preferably 5 mass% or more, from the viewpoints of the dielectric tangent and breaking elongation of the film.
[0016] -Polysulfone resin, polyethersulfone resin and polyphenylene sulfide resin- The polysulfone resin is a resin having a constitutional repeating unit containing a sulfonyl group (-S(=O)2-), and an example thereof is a resin obtained by desalting polycondensation of 4,4'-dichlorodiphenylsulfone (DCDPS) and the sodium salt of bisphenol A. The polysulfone resin is not particularly limited, and any known polysulfone resin can be used. Polyethersulfone resin is a resin having a constituent repeating unit containing a sulfonyl group (-S(=O)2-) and an ether bond (-O-), and an example thereof is a resin obtained by desalting polycondensation of 4,4'-dichlorodiphenylsulfone (DCDPS) and bisphenol S (Bis-S). The polyethersulfone resin is not particularly limited, and any known polyethersulfone resin can be used. Polyphenylene sulfide resin is a resin in which benzene rings and sulfur atoms are bonded alternately. The polyphenylene sulfide resin is not particularly limited, and any known polyphenylene sulfide resin can be used.
[0017] -Liquid crystal polymer- From the viewpoint of the dielectric loss tangent of the film, the resin is preferably a liquid crystal polymer. In the present disclosure, the liquid crystal polymer preferably has a dielectric loss tangent of 0.01 or less. The type of the liquid crystal polymer is not particularly limited, and any known liquid crystal polymer can be used. The liquid crystal polymer may be a thermotropic liquid crystal polymer that exhibits liquid crystallinity in a molten state, or a lyotropic liquid crystal polymer that exhibits liquid crystallinity in a solution state. In the case of a thermotropic liquid crystal, it is preferable that the liquid crystal polymer melts at a temperature of 450° C. or less. Examples of the liquid crystal polymer include liquid crystal polyester, liquid crystal polyester amide in which an amide bond is introduced into a liquid crystal polyester, liquid crystal polyester ether in which an ether bond is introduced into a liquid crystal polyester, and liquid crystal polyester carbonate in which a carbonate bond is introduced into a liquid crystal polyester. From the viewpoints of liquid crystallinity and linear expansion coefficient, the liquid crystal polymer is preferably a polymer having an aromatic ring, and more preferably an aromatic polyester or an aromatic polyester amide. Furthermore, the liquid crystal polymer may be a polymer in which an imide bond, a carbodiimide bond, or a bond derived from an isocyanate such as an isocyanurate bond is further introduced into an aromatic polyester or an aromatic polyester amide. The liquid crystal polymer is preferably a wholly aromatic liquid crystal polymer made using only aromatic compounds as raw material monomers.
[0018] Examples of liquid crystal polymers include, for example: 1) (i) A compound obtained by polycondensation of an aromatic hydroxycarboxylic acid, (ii) an aromatic dicarboxylic acid, and (iii) at least one compound selected from the group consisting of an aromatic diol, an aromatic hydroxyamine, and an aromatic diamine. 2) Those obtained by polycondensation of multiple types of aromatic hydroxycarboxylic acids. 3) (i) a polycondensation product of an aromatic dicarboxylic acid and (ii) at least one compound selected from the group consisting of an aromatic diol, an aromatic hydroxyamine, and an aromatic diamine. 4) (i) Polyester such as polyethylene terephthalate and (ii) aromatic hydroxycarboxylic acid are polycondensed. Here, the aromatic hydroxycarboxylic acid, aromatic dicarboxylic acid, aromatic diol, aromatic hydroxyamine and aromatic diamine may each independently be replaced in whole or in part by a polycondensable derivative thereof.
[0019] Examples of polymerizable derivatives of compounds having a carboxy group, such as aromatic hydroxycarboxylic acids and aromatic dicarboxylic acids, include those in which the carboxy group has been converted to an alkoxycarbonyl group or an aryloxycarbonyl group (esters), those in which the carboxy group has been converted to a haloformyl group (acid halides), and those in which the carboxy group has been converted to an acyloxycarbonyl group (acid anhydrides). Examples of polymerizable derivatives of compounds having a hydroxy group, such as aromatic hydroxycarboxylic acids, aromatic diols and aromatic hydroxyamines, include those obtained by acylation of a hydroxy group into an acyloxy group (acylated products). Examples of polymerizable derivatives of compounds having an amino group, such as aromatic hydroxyamines and aromatic diamines, include those obtained by acylation of the amino group to an acylamino group (acylated product).
[0020] From the viewpoints of liquid crystallinity, dielectric tangent of the film, and adhesion to a metal foil or metal wiring, the liquid crystal polymer preferably has a repeating unit represented by any one of the following formulas (1) to (3) (hereinafter, the repeating unit represented by formula (1) etc. may be referred to as repeating unit (1) etc.), more preferably has a repeating unit represented by the following formula (1), and particularly preferably has a repeating unit represented by the following formula (1), a repeating unit represented by the following formula (2), and a repeating unit represented by the following formula (2). Formula (1) -O-Ar 1 -CO- Formula (2) -CO-Ar 2 -CO- Formula (3) -X-Ar 3 -Y- In formulas (1) to (3), Ar 1 represents a phenylene group, a naphthylene group, or a biphenylylene group; Ar 2 and Ar 3 each independently represents a phenylene group, a naphthylene group, a biphenylylene group, or a group represented by the following formula (4), X and Y each independently represent an oxygen atom or an imino group, Ar 1 ~Ar 3 Each hydrogen atom in the above group represented by the formula: may be independently substituted with a halogen atom, an alkyl group or an aryl group. Formula (4) -Ar 4 -Z-Ar 5 - In formula (4), Ar 4 and Ar 5 each independently represents a phenylene group or a naphthylene group, and Z represents an oxygen atom, a sulfur atom, a carbonyl group, a sulfonyl group, or an alkylene group.
[0021] The halogen atom includes a fluorine atom, a chlorine atom, a bromine atom and an iodine atom. Examples of the alkyl group include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a s-butyl group, a t-butyl group, an n-hexyl group, a 2-ethylhexyl group, an n-octyl group, and an n-decyl group, and the number of carbon atoms is preferably 1 to 10. Examples of the aryl group include a phenyl group, an o-tolyl group, a m-tolyl group, a p-tolyl group, a 1-naphthyl group, and a 2-naphthyl group, and the number of carbon atoms is preferably 6 to 20. When the hydrogen atoms are replaced with these groups, the number of them is Ar 1 , Ar 2 Or Ar 3 The number of each of the above groups represented by the following formula (I) is preferably 2 or less, and more preferably 1.
[0022] Examples of the alkylene group include a methylene group, a 1,1-ethanediyl group, a 1-methyl-1,1-ethanediyl group, a 1,1-butanediyl group, and a 2-ethyl-1,1-hexanediyl group, and the number of carbon atoms is preferably 1 to 10.
[0023] The repeating unit (1) is a constituent repeating unit derived from a specific aromatic hydroxycarboxylic acid. The repeating unit (1) is Ar 1 is a p-phenylene group (constituent repeating unit derived from p-hydroxybenzoic acid), and Ar 1 is preferably a 2,6-naphthylene group (a repeating unit derived from 6-hydroxy-2-naphthoic acid) or a 4,4'-biphenylylene group (a repeating unit derived from 4'-hydroxy-4-biphenylcarboxylic acid).
[0024] The repeating unit (2) is a constituent repeating unit derived from a specific aromatic dicarboxylic acid. Repeating unit (2) is Ar 2 is a p-phenylene group (constituent repeating unit derived from terephthalic acid), Ar 2 is an m-phenylene group (a repeating unit derived from isophthalic acid), Ar 2 is a 2,6-naphthylene group (a repeating unit derived from 2,6-naphthalenedicarboxylic acid), or Ar 2 is a diphenylether-4,4'-diyl group (constituent repeating unit derived from diphenylether-4,4'-dicarboxylic acid).
[0025] The repeating unit (3) is a constituent repeating unit derived from a specific aromatic diol, aromatic hydroxylamine or aromatic diamine. Repeating unit (3) is Ar 3 is a p-phenylene group (constituent repeating units derived from hydroquinone, p-aminophenol or p-phenylenediamine), Ar 3is an m-phenylene group (a repeating unit derived from isophthalic acid), or Ar 3 is a 4,4'-biphenylylene group (a repeating unit derived from 4,4'-dihydroxybiphenyl, 4-amino-4'-hydroxybiphenyl or 4,4'-diaminobiphenyl).
[0026] The content of the repeating unit (1) is preferably 30 mol % or more, more preferably 30 mol % to 80 mol %, even more preferably 30 mol % to 60 mol %, and particularly preferably 30 mol % to 40 mol %, based on the total amount of all constituent repeating units (the mass of each constituent repeating unit constituting the liquid crystal polymer is divided by the formula weight of that repeating unit to determine the substance amount equivalent (mol) of each repeating unit, and the total value). The content of the repeating unit (2) is preferably 35 mol % or less, more preferably 10 mol % to 35 mol %, even more preferably 20 mol % to 35 mol %, and particularly preferably 30 mol % to 35 mol %, based on the total amount of all constituent repeating units. The content of the repeating unit (3) is preferably 35 mol % or less, more preferably 10 mol % to 35 mol %, still more preferably 20 mol % to 35 mol %, and particularly preferably 30 mol % to 35 mol %, based on the total amount of all constituent repeating units. The greater the content of the repeating unit (1), the more likely it is that the heat resistance, strength and rigidity will improve. However, if the content is too high, the solubility in solvents will tend to decrease.
[0027] The ratio of the content of the repeating unit (2) to the content of the repeating unit (3), expressed as [content of the repeating unit (2)] / [content of the repeating unit (3)] (mol / mol), is preferably 0.9 / 1 to 1 / 0.9, more preferably 0.95 / 1 to 1 / 0.95, and even more preferably 0.98 / 1 to 1 / 0.98.
[0028] The liquid crystal polymer may have two or more kinds of repeating units (1) to (3) independently. The liquid crystal polymer may have a constituent repeating unit other than the repeating units (1) to (3), but the content of such a repeating unit is preferably 10 mol % or less, more preferably 5 mol % or less, based on the total amount of all repeating units.
[0029] The liquid crystal polymer preferably has, as the repeating unit (3), at least one of X and Y being an imino group, i.e., at least one of a constituent repeating unit derived from a specific aromatic hydroxylamine and a constituent repeating unit derived from an aromatic diamine, since this has excellent solubility in a solvent, and more preferably has, as the repeating unit (3), only those in which at least one of X and Y is an imino group.
[0030] The liquid crystal polymer is preferably produced by melt-polymerizing the raw material monomers corresponding to the repeating units constituting the polymer. The melt-polymerization may be carried out in the presence of a catalyst, and examples of the catalyst include metal compounds such as magnesium acetate, stannous acetate, tetrabutyl titanate, lead acetate, sodium acetate, potassium acetate, and antimony trioxide, and nitrogen-containing heterocyclic compounds such as 4-(dimethylamino)pyridine and 1-methylimidazole, and nitrogen-containing heterocyclic compounds are preferably used. The melt-polymerization may be further carried out as necessary by solid-phase polymerization.
[0031] The liquid crystal polymer has a flow initiation temperature of preferably 250° C. or higher, more preferably 250° C. or higher and 350° C. or lower, and further preferably 260° C. or higher and 330° C. or lower. When the flow initiation temperature of the liquid crystal polymer is within the above range, the liquid crystal polymer has excellent solubility, heat resistance, strength and rigidity, and the viscosity of the solution is appropriate.
[0032] The flow initiation temperature is also called the flow temperature or flow temperature, and is measured using a capillary rheometer at 9.8 MPa (100 kg / cm 2When a liquid crystal polymer is melted and extruded from a nozzle with an inner diameter of 1 mm and a length of 10 mm while heating at a rate of 4°C / min under a load of 100 g / mol / L, the temperature at which the polymer shows a viscosity of 4,800 Pa s (48,000 poise) is reached, and this temperature is an indication of the molecular weight of liquid crystal polyester (see "Liquid Crystal Polymer - Synthesis, Molding, Applications" edited by Koide Naoyuki, CMC Corporation, June 5, 1987, p. 95).
[0033] The liquid crystal polymer preferably has a weight average molecular weight of 1,000,000 or less, more preferably 3,000 to 300,000, even more preferably 5,000 to 100,000, and particularly preferably 5,000 to 30,000. When the weight average molecular weight of the liquid crystal polymer is within the above range, the film after heat treatment has excellent thermal conductivity in the thickness direction, heat resistance, strength, and rigidity.
[0034] From the viewpoint of reducing transmission loss, the dielectric loss tangent of the liquid crystal polymer is preferably 0.01 or less, more preferably 0.005 or less, further preferably 0.004 or less, and particularly preferably 0.003 or less.
[0035] The method for measuring the dielectric loss tangent of a polymer film or resin in the present disclosure is as follows. The dielectric loss tangent is measured by the resonance perturbation method at a frequency of 10 GHz. A 10 GHz cavity resonator (Kanto Electronics Application Development Co., Ltd. CP531) is connected to a network analyzer (Agilent Technology's "E8363B"), and a film or resin sample (width: 2.0 mm x length: 80 mm) is inserted into the cavity resonator. The dielectric loss tangent of the film or resin is measured from the change in resonance frequency before and after insertion in an environment with a temperature of 25°C and a humidity of 60%. The copper foil is removed with ferric chloride before measurement.
[0036] The polymer film according to the present disclosure may contain only one type of the above resin, or may contain two or more types. The content of the resin in the polymer film according to the present disclosure is preferably 20% by mass to 99% by mass, more preferably 30% by mass to 98% by mass, and particularly preferably 40% by mass to 95% by mass, relative to the total mass of the film, from the viewpoints of the dielectric tangent of the film and adhesion to a metal foil or metal wiring.
[0037] <<Liquid crystal polymer particles>> The particle-containing layer contains liquid crystal polymer particles, and the content of the liquid crystal polymer particles in the particle-containing layer is 40 volume % or more. From the viewpoint of the dielectric loss tangent and breaking elongation of the film, the liquid crystal polymer particles preferably have low solubility in organic solvents and are preferably substantially insoluble. Specifically, for example, the solubility in N-methylpyrrolidone at 140° C. is preferably 1% by mass or less, more preferably 0.5% by mass or less, and particularly preferably 0.1% by mass or less. The preferred embodiments of the liquid crystal polymer in the liquid crystal polymer particles of the present disclosure are the same as the preferred embodiments of the liquid crystal polymer described above.
[0038] From the viewpoint of reducing the dielectric tangent of the particle-containing layer, the liquid crystal polymer particles preferably have a dielectric tangent smaller than that of at least one resin selected from the group consisting of the liquid crystal polymer, polysulfone resin, polyethersulfone resin, and polyphenylene sulfide resin. The dielectric loss tangent of the liquid crystal polymer particles is preferably 0.01 or less, more preferably 0.005 or less, further preferably 0.004 or less, and particularly preferably more than 0 and 0.003 or less. The dielectric loss tangent of the liquid crystal polymer particles is measured by the above-mentioned method using a green compact sample (width: 2.0 mm×length: 80 mm) produced by compression molding.
[0039] The median diameter (D50) of the liquid crystal polymer particles is not particularly limited and may be appropriately selected as desired. From the viewpoints of dispersibility and tensile strength, however, it is preferably 0.01 μm to 100 μm, more preferably 0.05 μm to 50 μm, even more preferably 0.1 μm to 30 μm, and particularly preferably 1 μm to 20 μm.
[0040] In the present disclosure, the median particle size refers to the diameter at which the total volume of particles on the larger diameter side and the smaller diameter side are equal when the entire liquid crystal polymer particles are divided into two parts with a particle size at which the cumulative volume is 50%. In the present disclosure, the median particle size is measured using a Microtrac MT3300EXII (manufactured by Nikkiso Co., Ltd.).
[0041] From the viewpoint of the breaking elongation of the film, it is preferable that the liquid crystal polymer particles contain liquid crystal polymer particles whose surfaces have been subjected to an oxidation treatment. The method for producing liquid crystal polymer particles having a surface oxidizing treatment is not particularly limited, but preferably includes an oxidation treatment step of oxidizing the surface of the liquid crystal polymer particles.
[0042] -Oxidation treatment process- The oxidation treatment step is preferably a step of oxidizing the surfaces of the liquid crystal polymer particles using an oxidizing agent, and more preferably a step of contacting the liquid crystal polymer particles with an oxidizing agent in an aqueous solution to oxidize the surfaces of the liquid crystal polymer particles. The pH of the aqueous solution is not particularly limited as long as it is capable of oxidation, but is preferably 8 or higher, more preferably 12 or higher, and even more preferably 13 or higher. There is no upper limit to the pH of the aqueous solution, and it is, for example, 14.
[0043] The time for which the liquid crystal polymer particles are contacted with the oxidizing agent in the aqueous solution is preferably from 0.1 to 24 hours, more preferably from 0.5 to 10 hours, and even more preferably from 1.5 to 6 hours. The temperature of the aqueous solution when the liquid crystal polymer particles are brought into contact with the oxidizing agent is preferably from 1°C to 95°C, more preferably from 25°C to 80°C, and even more preferably from 45°C to 65°C.
[0044] There are no limitations on the method of contacting the liquid crystal polymer particles with the oxidizing agent in the aqueous solution, and examples of the method include a method of contacting the liquid crystal polymer particles with the oxidizing agent by mixing using a grinding machine or disintegrator such as a rocking mill, a piece mill, a ball mill, a Henschel mixer, a jet mill, a Starburst, or a paint conditioner, a method of contacting the liquid crystal polymer particles with the oxidizing agent while stirring using a mechanical stirrer such as a Three-One Motor or a magnetic stirrer, and a method of contacting the liquid crystal polymer particles with an aqueous oxidizing agent solution containing an oxidizing agent, etc., circulated by a pump through a cartridge filled with the liquid crystal polymer particles. During the above-mentioned method of contacting while circulating, even if a portion of the aqueous oxidant solution is in contact with the liquid crystal polymer particles filled in the cartridge and another portion of the aqueous oxidant solution is present in the pump or the like and is not in contact with the liquid crystal polymer particles, all of the liquid crystal polymer particles and the aqueous oxidant solution subjected to the modification step are considered to be the above-mentioned aqueous solution as a whole.
[0045] It is preferable that after the liquid crystal polymer particles are contacted with the oxidizing agent in the aqueous solution, the resulting liquid crystal polymer particles are taken out from the aqueous solution. The method for extracting the liquid crystal polymer particles from the aqueous solution is not particularly limited, and any known method can be used. For example, the aqueous solution is filtered to separate the liquid crystal polymer particles as a residue. It is also preferable to wash the liquid crystal polymer particles taken out with water, an organic solvent or the like.
[0046] -Oxidizing agent- In the oxidation treatment step, it is preferable to use an oxidizing agent. The aqueous solution preferably contains an oxidizing agent. The oxidizing agent is not limited, and examples thereof include persulfates such as sodium persulfate, potassium persulfate, and ammonium persulfate; nitrates such as cerium ammonium nitrate, sodium nitrate, and ammonium nitrate; peroxides such as hydrogen peroxide and tert-butyl hydroperoxide; manganese compounds such as potassium permanganate and manganese dioxide; chromium compounds such as potassium chromate and potassium dichromate; hypervalent iodine compounds such as potassium periodate and sodium periodate; quinone compounds such as p-benzoquinone, 1,2-naphthoquinone, anthraquinone, and chloranil; amine oxide compounds such as N-methylmorpholine N-oxide, salts of halogen oxo acids such as sodium hypochlorite and sodium chlorite, and double salts of potassium peroxymonosulfate-potassium hydrogen sulfate-potassium sulfate (OXONE manufactured by DuPont). Among these, from the viewpoints of oxidizing property, dispersibility, and tensile strength, the oxidizing agent preferably contains a persulfate, and is more preferably a persulfate. From the viewpoint of oxidizing ability, the oxidizing agent preferably contains at least one compound selected from the group consisting of sodium persulfate, potassium persulfate, ammonium persulfate, hydrogen peroxide, potassium permanganate, sodium hypochlorite, ammonium cerium nitrate, potassium chromate, potassium dichromate, and a double salt of potassium peroxymonosulfate-potassium hydrogen sulfate-potassium sulfate, more preferably contains at least one compound selected from the group consisting of sodium persulfate, potassium persulfate, ammonium persulfate, hydrogen peroxide, sodium hypochlorite, ammonium cerium nitrate, and a double salt of potassium peroxymonosulfate-potassium hydrogen sulfate-potassium sulfate, and particularly preferably contains at least one compound selected from the group consisting of sodium persulfate, potassium persulfate, and ammonium persulfate.
[0047] In addition, a catalyst may be used in addition to the oxidizing agent to assist the action of the oxidizing agent. Examples of the catalyst include divalent iron compounds (FeSO4, etc.) and trivalent iron compounds. The oxidizing agent and the catalyst may each be a hydrate.
[0048] From the viewpoint of oxidizing property, the standard redox potential of the oxidizing agent is preferably 0.30 V or more, more preferably 1.50 V or more, and even more preferably 1.70 V or more. There is no particular upper limit to the standard redox potential of the oxidizing agent, and it is, for example, preferably 4.00 V or less, and more preferably 2.50 V or less. The above standard oxidation-reduction potentials are based on the standard hydrogen electrode.
[0049] The content of the oxidizing agent in the aqueous solution is preferably 0.05 to 20 parts by mass, more preferably 0.1 to 20 parts by mass, and particularly preferably 1 to 20 parts by mass, relative to 100 parts by mass of water in the aqueous solution. The oxidizing agent may be used alone or in combination of two or more kinds. When the aqueous solution contains a catalyst, the content of the oxidizing agent is preferably 0.005 to 2 parts by mass, more preferably 0.01 to 2 parts by mass, and even more preferably 0.1 to 2 parts by mass, per 100 parts by mass of water in the aqueous solution. The catalyst may be used alone or in combination of two or more.
[0050] -Alkaline compounds- The aqueous solution preferably contains an alkaline compound in addition to the above-mentioned components in order to adjust the pH of the aqueous solution. Examples of the alkaline compound include inorganic bases such as alkali metal hydroxides (such as sodium hydroxide) and alkaline earth metal hydroxides, and organic bases. Among these, alkali metal hydroxides are preferred. The content of the alkaline compound in the aqueous solution may be appropriately adjusted so that the pH of the aqueous solution can be adjusted to a desired temperature. For example, the content is preferably 0.1 to 10 parts by mass per 100 parts by mass of water in the aqueous solution.
[0051] The method for producing liquid crystal polymer particles having a surface oxidized may include other steps. The method for producing liquid crystal polymer particles preferably includes a step of preparing liquid crystal polymer particles to be used in the oxidation treatment step. The liquid crystal polymer particles used in the oxidation treatment step may be prepared by a known method, or a commercially available product may be used. The method for producing liquid crystal polymer particles may also include a washing step of washing the liquid crystal polymer particles obtained by the oxidation treatment step, and a drying step of drying the liquid crystal polymer particles obtained by the oxidation treatment step or the washing step. The washing method in the washing step and the drying method in the drying step are not particularly limited, and any known method can be used.
[0052] -Other additives- The liquid crystal polymer particles may contain other additives. As the other additives, known additives can be used, specifically, for example, fillers, leveling agents, antifoaming agents, antioxidants, ultraviolet absorbers, flame retardants, colorants, etc.
[0053] Furthermore, as other additives, resins other than the above-mentioned components may be contained. Examples of resins other than liquid crystal polymers include thermoplastic resins such as polyolefins, cycloolefin polymers, polyamides, polyesters, polyether ketones, polycarbonates, polyphenylene ethers and modified products thereof, and polyetherimides; elastomers such as copolymers of glycidyl methacrylate and polyethylene; and thermosetting resins such as phenolic resins, epoxy resins, polyimide resins, and cyanate resins.
[0054] The total content of other additives is preferably 25 parts by mass or less, more preferably 10 parts by mass or less, and further preferably 5 parts by mass or less, based on 100 parts by mass of the liquid crystal polymer.
[0055] In the polymer film according to the present disclosure, the liquid crystal polymer particles may be used alone or in combination of two or more kinds. The content of the liquid crystal polymer particles in the particle-containing layer is 40% by volume or more, and from the viewpoints of the dielectric tangent and breaking elongation of the film, it is preferably 45 to 80% by volume, more preferably 50 to 75% by volume, even more preferably 50 to 70% by volume, and particularly preferably 55 to 70% by volume. The content of liquid crystal polymer particles can be measured by immersing the polymer film in a large excess of an organic solvent, heating it to dissolve it, and then filtering out the liquid crystal polymer particles that are not dissolved in the organic solvent.
[0056] -Other additives- The polymeric films according to the present disclosure may also contain other additives. As the other additives, known additives can be used, specifically, for example, a leveling agent, a defoaming agent, an antioxidant, an ultraviolet absorbing agent, a flame retardant, a colorant, a filler other than the liquid crystal polymer particles, and the like.
[0057] The total content of other additives is preferably 25 parts by mass or less, more preferably 10 parts by mass or less, and even more preferably 5 parts by mass or less, based on 100 parts by mass of the total content of the resin and the liquid crystal polymer particles.
[0058] The average thickness of the particle-containing layer is not particularly limited, but is preferably from 5 μm to 200 μm, more preferably from 10 μm to 150 μm, and even more preferably from 20 μm to 120 μm.
[0059] The average thickness of each layer in the polymer film according to the present disclosure is measured using the following method. The wiring board is cut with a microtome, and the cross section is observed under an optical microscope to evaluate the thickness of each layer. Cross-sectional samples are cut out in three or more places, and the thickness is measured at three or more points on each cross section, and the average of these is taken as the average thickness.
[0060] <Dielectric tangent> From the viewpoint of reducing transmission loss of the produced substrate, the polymer film according to the present disclosure has a dielectric tangent of 0.01 or less, preferably 0.005 or less, more preferably 0.004 or less, even more preferably 0.0035 or less, and particularly preferably 0.003 or less.
[0061] <Thermal expansion coefficient> From the viewpoint of thermal stability, the thermal expansion coefficient of the polymer film according to the present disclosure is preferably from −20 ppm / K to 100 ppm / K, and more preferably from 0 ppm / K to 80 ppm / K.
[0062] The thermal expansion coefficient in the present disclosure is measured by the following method. Using a thermomechanical analyzer (TMA), a tensile load of 1 g is applied to both ends of a film with a width of 5 mm and a length of 20 mm, and the film is heated from 25°C to 200°C at a rate of 5°C / min, cooled to 30°C at a rate of 2°C / min, and then heated again at a rate of 5°C / min. The thermal expansion coefficient is calculated from the slope of the TMA curve between 30°C and 150°C. Note that the copper foil is removed with ferric chloride before the measurement.
[0063] <Surface roughness> The polymer film according to the present disclosure has a surface roughness Rz of at least one surface of preferably 10 nm to 10,000 nm, more preferably 10 nm to 5,000 nm, even more preferably 20 nm to 1,000 nm, and still more preferably 50 nm to 500 nm.
[0064] In this disclosure, "surface roughness Rz" refers to the sum of the maximum peak height and the maximum valley depth observed on a roughness curve over a reference length, expressed in nanometers. In the present disclosure, the surface roughness Rz of the film surface is measured by the following method. A non-contact surface / layer cross-sectional shape measurement system, VertScan (manufactured by Ryoka Systems Co., Ltd.), is used to measure an area 465.48 μm long and 620.64 μm wide, and a roughness curve and the average line of the roughness curve for the surface of the measurement object (liquid crystal polymer film) are created. A portion corresponding to the reference length is extracted from the roughness curve. The surface roughness Rz of the measurement object is measured by calculating the sum of the maximum peak height (i.e., the height from the average line to the peak) and the maximum valley depth (i.e., the height from the average line to the valley bottom) observed on the extracted roughness curve.
[0065] Methods for forming a film having a surface roughness Rz of 10 nm to 10,000 nm include, for example, a method of generating Benard cells during film formation, a method of using a solution containing a filler and a liquid crystal polymer, a method of phase-separating a material mixed with a liquid crystal polymer during film formation, a method of forming a skin on the surface during the film formation process and using the difference in the amount of shrinkage with the inside (reticulation), a method of performing a replica process using a mold with an uneven surface during solution film formation, and a method of roughening the film after film formation by surface treatment such as sputtering.
[0066] <Elasticity modulus> The elastic modulus at 25° C. of at least one surface of the polymer film according to the present disclosure is preferably 10 MPa or more from the viewpoints of mechanical strength and prevention of fracture failure during peeling. Furthermore, it is preferable that a surface that satisfies the above elastic modulus range is a surface that satisfies the above surface free energy range, a surface that satisfies the above surface coverage range, or a surface that satisfies the above surface free energy range and the above surface coverage range.
[0067] In the present disclosure, the elastic modulus of a film surface is measured by the following method. The elastic modulus of the film surface is determined using a microsurface hardness tester (Fisherscope H100VP-HCU, manufactured by Fisher Instruments, Inc.). Specifically, a diamond pyramid indenter (tip facing angle: 136°) is used to measure the indentation depth under an appropriate test load at 25°C within a range not exceeding 1 μm, and the storage elastic modulus is calculated from the change in load and displacement when the load is removed.
[0068] The polymer film according to the present disclosure may have a single layer structure or a multilayer structure. The polymer film according to the present disclosure may be used as a membrane provided on a substrate such as a metal substrate. The polymer film according to the present disclosure preferably includes, for example, a layer A which is a particle-containing layer, and a layer B which is disposed on the layer A and contains a polymer and a curable compound described later. For example, a polymer film having excellent adhesion can be obtained by bonding the layer A side of the film to a metal substrate.
[0069] The content of the polymer in Layer A is preferably from 25% by mass to 99% by mass, and more preferably from 40% by mass to 60% by mass, based on the total mass of Layer A.
[0070] The average thickness of layer A is not particularly limited, but is preferably from 5 μm to 200 μm, more preferably from 10 μm to 150 μm, and even more preferably from 20 μm to 120 μm.
[0071] Preferred embodiments of the polymer used in Layer B are the same as the preferred embodiments of the polymer described above, except as described above.
[0072] The content of the curable compound in Layer B is preferably from 5% by mass to 75% by mass, and more preferably from 10% by mass to 50% by mass, based on the total mass of Layer B.
[0073] The average thickness of Layer B is not particularly limited, but is preferably from 1 μm to 50 μm, and more preferably from 10 μm to 30 μm.
[0074] Layer A and Layer B may each independently contain other additives. The preferred embodiments of the other additives used in Layer A or Layer B are the same as those described above.
[0075] -Curable compound- Layer B preferably contains a curable compound, and more preferably the curable compound contains a curable compound A which is an oligomer or a polymer. The curable compound in the present disclosure is a compound having a curable group, and may be any of a monomer, an oligomer, and a polymer. The curable compound A is an oligomer or a polymer, and is preferably a polymer from the viewpoint of mechanical strength. In the present disclosure, an oligomer is a polymer having a weight average molecular weight of 1,000 or more and less than 2,000, and a polymer is a polymer having a weight average molecular weight of 2,000 or more. From the viewpoints of adhesion and uneven distribution to the metal foil or metal wiring, the curable compound A is preferably an oligomer or polymer having a weight-average molecular weight of 1,000 or more, more preferably a polymer having a weight-average molecular weight of 2,000 or more, even more preferably a polymer having a weight-average molecular weight of 3,000 or more and 200,000 or less, and particularly preferably a polymer having a weight-average molecular weight of 5,000 or more and 100,000 or less. Furthermore, from the viewpoint of suppressing wiring distortion, the weight average molecular weight of the curable compound A is preferably 100,000 or less, more preferably 50,000 or less, and particularly preferably 10,000 or less. The polymer having a dielectric loss tangent of 0.01 or less may have a curable group, but is a compound different from the curable compound A. The curable compound A preferably has a dielectric loss tangent of more than 0.01 and is preferably not a liquid crystal polymer.
[0076] In addition, from the viewpoint of suppressing wiring distortion, the polymer film according to the present disclosure preferably has a higher content of the curable compound A on at least one surface of the film than in the interior thereof. Furthermore, from the viewpoint of suppressing wiring distortion, it is preferable that Layer A contains particles, and the particles contain the curable compound inside or on the surface thereof. The above particles include microcapsules or microgels having the above curable compound inside or on the surface thereof. Among these, preferred examples include microcapsules or microgels having the above-mentioned curable compound therein. The particles are preferably organic resin particles.
[0077] The number of curable groups in the curable compound may be 1 or more, and may be 2 or more, but is preferably 2 or more. Furthermore, the curable compound may have only one type of curable group, or may have two or more types of curable groups.
[0078] The curable group is not particularly limited as long as it is curable, and examples thereof include an ethylenically unsaturated group, an epoxy group, an oxetanyl group, an isocyanate group, an acid anhydride group, a carbodiimide group, an N-hydroxyester group, a glyoxal group, an imide ester group, a halogenated alkyl group, a thiol group, a hydroxy group, a carboxy group, an amino group, an amide group, an aldehyde group, and a sulfonic acid group. When the curable compound A is formed by half curing, which will be described later, the curable group is preferably an ethylenically unsaturated group. In this case, the curable compound is preferably a polyfunctional ethylenically unsaturated compound.
[0079] The curable compound A is preferably a thermosetting resin. Examples of the thermosetting resin include epoxy resin, phenol resin, unsaturated imide resin, cyanate resin, isocyanate resin, benzoxazine resin, oxetane resin, amino resin, unsaturated polyester resin, allyl resin, dicyclopentadiene resin, silicone resin, triazine resin, and melamine resin. The thermosetting resin is not particularly limited to these, and any known thermosetting resin can be used. These thermosetting resins can be used alone or in combination. As the curable compound A, a commercially available adhesive (so-called varnish or hot melt adhesive, etc.) can also be used.
[0080] As the curable compound A, a curable compound obtained by half-curing a monomer is preferably used. The monomer is preferably an ethylenically unsaturated compound, more preferably a polyfunctional ethylenic compound. Examples of the ethylenically unsaturated compound include a (meth)acrylate compound, a (meth)acrylamide compound, a (meth)acrylic acid, a styrene compound, a vinyl acetate compound, a vinyl ether compound, and an olefin compound. Of these, (meth)acrylate compounds are preferred. From the viewpoint of adhesion to metal foil or metal wiring, the molecular weight of the monomer is preferably 50 or more and less than 1,000, more preferably 100 or more and less than 1,000, and particularly preferably 200 or more and 800 or less.
[0081] In addition, when the curable compound includes an ethylenically unsaturated compound, the polymer film according to the present disclosure preferably includes a polymerization initiator. The polymerization initiator is preferably a thermal polymerization initiator or a photopolymerization initiator. As the thermal polymerization initiator or photopolymerization initiator, known initiators can be used. The thermal polymerization initiator may be a thermal radical generator, specifically, a peroxide initiator such as benzoyl peroxide or azobisisobutyronitrile, or an azo-based initiator. Examples of the photopolymerization initiator include photoradical generators, specifically, (a) aromatic ketones, (b) onium salt compounds, (c) organic peroxides, (d) thio compounds, (e) hexaarylbiimidazole compounds, (f) ketoxime ester compounds, (g) borate compounds, (h) azinium compounds, (i) active ester compounds, (j) compounds having a carbon-halogen bond, and (k) pyridium compounds. The polymerization initiator may be added alone or in combination of two or more kinds. The content of the polymerization initiator is preferably from 0.01% by mass to 30% by mass, more preferably from 0.05% by mass to 25% by mass, and further preferably from 0.1% by mass to 20% by mass, based on the total mass of the curable compound.
[0082] Layer B may contain only one type of curable compound, for example only one type of curable compound A, or may contain two or more types of curable compounds. Furthermore, the layer B may contain only one type of the curable compound A, or may contain two or more types. The content of the curable compound in Layer B is preferably 0.1% by mass to 70% by mass, more preferably 1% by mass to 60% by mass, further preferably 5% by mass to 60% by mass, and particularly preferably 10% by mass to 55% by mass, relative to the total mass of Layer B, from the viewpoints of the dielectric tangent of the film and the ability to suppress wiring distortion. From the viewpoints of the dielectric tangent of the film and the wiring distortion suppression property, the content of the curable compound A in Layer B is preferably 0.1 mass % to 70 mass %, more preferably 1 mass % to 60 mass %, further preferably 5 mass % to 60 mass %, and particularly preferably 10 mass % to 55 mass %, relative to the total mass of Layer B.
[0083] From the viewpoint of suppressing wiring distortion, the content of the curable compound A in layer B is preferably 30% by mass to 100% by mass, more preferably 50% by mass to 100% by mass, and particularly preferably 70% by mass to 100% by mass, based on the total mass of the curable compound.
[0084] - Hardening inhibitors - From the viewpoints of controlling the curing state and suppressing wiring distortion, it is preferable that Layer B contains a curing inhibitor. Examples of the curing inhibitor include a polymerization inhibitor and a heat stabilizer, each of which may be a known agent. Examples of the polymerization inhibitor include p-methoxyphenol, quinones (e.g., hydroquinone, benzoquinone, methoxybenzoquinone, etc.), phenothiazine, catechols, alkylphenols (e.g., dibutylhydroxytoluene (BHT)), alkylbisphenols, zinc dimethyldithiocarbamate, copper dimethyldithiocarbamate, copper dibutyldithiocarbamate, copper salicylate, thiodipropionic acid esters, mercaptobenzimidazole, phosphites, 2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO), 2,2,6,6-tetramethyl-4-hydroxypiperidine-1-oxyl (TEMPOL), and tris(N-nitroso-N-phenylhydroxylamine) aluminum salt (also known as Cupferron Al). Examples of the heat stabilizer include phosphorus-based heat stabilizers such as tris(2,4-di-tert-butylphenyl)phosphite, bis[2,4-bis(1,1-dimethylethyl)-6-methylphenyl]ethyl ester phosphorous acid, tetrakis(2,4-di-tert-butylphenyl)[1,1-biphenyl]-4,4'-diylbisphosphonite, and bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, and lactone-based heat stabilizers such as a reaction product of 8-hydroxy-5,7-di-tert-butyl-furan-2-one and o-xylene.
[0085] The curing inhibitor may be used alone or in combination of two or more kinds. The content of the curing inhibitor is not particularly limited, but is preferably 0.0001% by mass to 2.0% by mass relative to the total mass of Layer B.
[0086] The average thickness of the polymer film according to the present disclosure is preferably 6 μm to 200 μm, more preferably 12 μm to 100 μm, and particularly preferably 20 μm to 60 μm, from the viewpoints of strength, thermal expansion coefficient, and adhesion to metal foil or metal wiring.
[0087] The average thickness of the polymer film is determined by measuring any five points using an adhesive film thickness meter, for example, an electronic micrometer (product name "KG3001A" manufactured by Anritsu Corporation), and averaging these values.
[0088] <Application> The polymer film according to the present disclosure can be used for various applications, and among others, can be suitably used as a film for electronic components such as printed wiring boards, and can be even more suitably used for flexible printed circuit boards. Furthermore, the polymer film according to the present disclosure can be suitably used as a film for bonding metals.
[0089] (Method of manufacturing polymer film) A method for producing a polymer film according to the present disclosure includes a forming step of forming a particle-containing layer on a substrate by applying a polymer solution containing at least one resin selected from the group consisting of a liquid crystal polymer, a polysulfone resin, a polyethersulfone resin, and a polyphenylene sulfide resin, liquid crystal polymer particles, and an organic solvent onto the substrate and drying the solution, and a heating step of heating the particle-containing layer at a temperature equal to or higher than the glass transition temperature of the resin, wherein the content of the liquid crystal polymer particles in the particle-containing layer after the heating step is 40% by volume or more. The polymer film according to the present disclosure is preferably a polymer film produced by the polymer film production method according to the present disclosure.
[0090] In the method for producing a polymer film according to the present disclosure, the preferred aspects of the above-mentioned components among the components used, as well as the preferred aspects of the components and contents contained in the obtained polymer film, are the same as the preferred aspects of the polymer film according to the present disclosure described above. In addition, in the method for producing a polymer film according to the present disclosure, the amount of each component used is the same as the preferred amount corresponding to the preferred embodiment of the content of each component in the polymer film according to the present disclosure described above.
[0091] In the method for producing a polymer film according to the present disclosure, the preferred physical property values of the polymer film obtained are the same as those of the preferred aspects of the polymer film according to the present disclosure described above.
[0092] <Formation process> The method for producing a polymer film according to the present disclosure includes a forming step of applying a polymer solution containing at least one resin selected from the group consisting of a liquid crystal polymer, a polysulfone resin, a polyethersulfone resin, and a polyphenylene sulfide resin, liquid crystal polymer particles, and an organic solvent onto a substrate, and drying the applied solution to form a particle-containing layer on the substrate. The method for forming the particle-containing layer is not particularly limited, and known methods can be referred to, and for example, casting method, coating method, etc. are preferably mentioned, among which, casting method is particularly preferred. In addition, when the film has a multi-layer structure, for example, co-casting method, multi-layer coating method, etc. are preferably mentioned. Among them, co-casting method is particularly preferred for forming a relatively thin film. When a multilayer structure in a polymer film is produced by the co-casting method or the multi-layer coating method, it is preferable to carry out the co-casting method or the multi-layer coating method using a composition for forming layer A, a composition for forming layer B, etc., in which the components of each layer, such as a liquid crystal polymer, are dissolved or dispersed in an organic solvent.
[0093] Examples of the organic solvent include halogenated hydrocarbons such as dichloromethane, chloroform, 1,1-dichloroethane, 1,2-dichloroethane, 1,1,2,2-tetrachloroethane, 1-chlorobutane, chlorobenzene, and o-dichlorobenzene; halogenated phenols such as p-chlorophenol, pentachlorophenol, and pentafluorophenol; ethers such as diethyl ether, tetrahydrofuran, and 1,4-dioxane; ketones such as acetone and cyclohexanone; esters such as ethyl acetate and γ-butyrolactone; and ethylene carbonate. nitriles such as acetonitrile and succinonitrile; amides such as N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, and urea compounds such as tetramethylurea; nitro compounds such as nitromethane and nitrobenzene; sulfur compounds such as dimethyl sulfoxide and sulfolane; and phosphorus compounds such as hexamethylphosphoramide and tri-n-butylphosphoric acid, and two or more of these may be used.
[0094] As the organic solvent, since it is less corrosive and easy to handle, an organic solvent mainly composed of an aprotic compound, particularly an aprotic compound having no halogen atom, is preferred, and the ratio of the aprotic compound in the entire organic solvent is preferably 50% by mass to 100% by mass, more preferably 70% by mass to 100% by mass, and particularly preferably 90% by mass to 100% by mass. In addition, as the aprotic compound, since it is easy to dissolve the liquid crystal polymer, it is preferred to use amides such as N,N-dimethylformamide, N,N-dimethylacetamide, tetramethylurea, and N-methylpyrrolidone, or esters such as γ-butyrolactone, and N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone are more preferred, and N-methylpyrrolidone is particularly preferred.
[0095] As the organic solvent, a solvent mainly composed of a compound having a dipole moment of 3 to 5 is preferred because it easily dissolves the liquid crystal polymer, and the proportion of the compound having a dipole moment of 3 to 5 in the entire solvent is preferably 50% by mass to 100% by mass, more preferably 70% by mass to 100% by mass, and particularly preferably 90% by mass to 100% by mass. As the aprotic compound, a compound having a dipole moment of 3 to 5 is preferably used.
[0096] Furthermore, as the organic solvent, a solvent mainly composed of a compound having a boiling point of 220° C. or lower at 1 atmospheric pressure is preferred because it is easy to remove, and the proportion of the compound having a boiling point of 220° C. or lower at 1 atmospheric pressure in the entire solvent is preferably 50% by mass to 100% by mass, more preferably 70% by mass to 100% by mass, and particularly preferably 90% by mass to 100% by mass. As the aprotic compound, it is preferable to use a compound having a boiling point of 220° C. or lower at 1 atmospheric pressure.
[0097] In the above-mentioned film manufacturing method, a particle-containing layer is formed on a substrate. When a metal layer (metal foil) or the like used in a laminate described later is used as the substrate, the substrate may be used as it is without being peeled off. Examples of the substrate include a metal drum, a metal band, a glass plate, a resin film, and a metal foil. Among these, a metal drum, a metal band, and a resin film are preferred. An example of the resin film is a polyimide (PI) film. Examples of commercially available products include U-Pirex S and U-Pirex R manufactured by Ube Industries, Ltd., Kapton manufactured by DuPont-Toray Co., Ltd., and IF30, IF70, and LV300 manufactured by SKC Kolon PI. The substrate may have a surface treatment layer formed on its surface so that it can be easily peeled off. The surface treatment layer may be made of hard chrome plating, fluororesin, or the like. The average thickness of the resin film support is not particularly limited, but is preferably from 25 to 75 μm, and more preferably from 50 to 75 μm.
[0098] The method for removing at least a part of the solvent from the cast or coated film-like composition (cast film or coating film) is not particularly limited, and a known drying method can be used.
[0099] <Stretching process> The method for producing a polymer film according to the present disclosure may include a stretching step of stretching the film, and may also include a stretching step of stretching the film between the forming step and the heating step. In the method for producing a polymer film according to the present disclosure, stretching can be appropriately combined from the viewpoint of controlling the molecular orientation of the obtained film and adjusting the linear expansion coefficient and mechanical properties. The stretching method is not particularly limited, and known methods can be referred to. It may be performed in a state containing a solvent or in a dry film state. Stretching in a state containing a solvent may be performed by gripping the film and stretching it, or by using the self-shrinking force of the web due to drying without stretching it, or a combination thereof. Stretching is particularly effective for the purpose of improving the breaking elongation and breaking strength when the brittleness of the film is reduced by the addition of inorganic fillers, etc.
[0100] <Heating process> The method for producing a polymer film according to the present disclosure includes a heating step of heating the particle-containing layer at a temperature equal to or higher than the glass transition temperature of the resin. It is believed that the heating step promotes crystallization of the resin in the film, thereby lowering the dielectric tangent of the film. When a layer other than the particle-containing layer is also formed in the forming step, it is preferable to heat the layer other than the particle-containing layer together with the particle-containing layer in the heating step. In the method for producing a polymer film according to the present disclosure, the amount of dissolved oxygen is preferably 500 ppm or less, more preferably 300 ppm or less, at the start of heating the film. When the amount of dissolved oxygen is within the above range, a film with a lower dielectric loss tangent can be obtained. The above-mentioned heating start time refers to the time when application of heat to the film begins.
[0101] In the present disclosure, the amount of dissolved oxygen is measured using a dissolved oxygen meter, for example, the portable oxygen analyzer "ORBISPHERE 3650" manufactured by Hack Ultra.
[0102] The heating temperature in the heating step is preferably 100° C. to 400° C. The heating time is preferably 0.1 minutes to 10 hours. The heating temperature and heating time can be appropriately changed depending on the type of polymer, and can also be lowered or shortened by other means such as the addition of a catalyst.
[0103] The heating step may be carried out under an inert gas atmosphere or an atmosphere containing oxygen. From the viewpoint of production efficiency, the heating step is preferably carried out under an atmosphere having an oxygen concentration of 500 ppm or more, and more preferably under an air (air) atmosphere.
[0104] <Winding process> The method for producing a polymer film according to the present disclosure preferably includes a winding step of winding the film into a roll, and more preferably includes a winding step of winding the film into a roll after the forming step and before the heating step. The step of winding the film into a roll is preferably carried out under a nitrogen atmosphere, which can further reduce the amount of dissolved oxygen in the film at the start of heating the film.
[0105] <Unwinding process> The method for producing a polymer film according to the present disclosure preferably includes, after the winding step, an unwinding step of unwinding the rolled film. In addition, the peel force when unwinding the film in the unwinding step is preferably 1.0 kN / m or less.
[0106] <Peeling process> The method for producing a polymer film according to the present disclosure may include a peeling step of peeling the film from the substrate after the forming step or the heating step. By peeling the film from the substrate, a film is obtained and can be applied to other uses.
[0107] <Other processes> The method for producing a polymer film according to the present disclosure may include other steps in addition to those described above. Other steps may include known steps.
[0108] (Laminate) The laminate according to the present disclosure may be any laminate in which the polymer film according to the present disclosure is laminated, but it preferably has the polymer film according to the present disclosure and a metal layer or metal wiring, and it is more preferable that the laminate has the polymer film according to the present disclosure and a copper layer or copper wiring arranged on at least one surface of the film. In addition, it is preferable that the surface of the film on which the metal layer or metal wiring is arranged is a surface that satisfies the above-mentioned surface free energy range, a surface that satisfies the above-mentioned surface coverage range, or a surface that satisfies the above-mentioned surface free energy range and the above-mentioned surface coverage range.
[0109] The surface roughness Ra of the film-side surface of the metal layer or metal wiring is preferably 1.0 μm or less, more preferably 0.5 μm or less. If the surface roughness Ra is 1.0 μm or less, the surface resistance at the interface between the film and the metal substrate decreases.
[0110] The surface roughness Ra in this disclosure is calculated using a surface roughness meter, for example, a stylus-type surface roughness meter "SURFCORDER SE3500" manufactured by Kosaka Laboratory Ltd., based on the calculation method for arithmetic mean surface roughness Ra of JIS B0601:2013. In measuring the surface roughness Ra, the metal layer or metal wiring in the laminate is removed by etching using an iron chloride solution, and then the surface roughness Ra of the film surface that was in contact with the metal layer or metal wiring to which the surface roughness of the metal layer or metal wiring has been transferred is measured, and this is regarded as the surface roughness Ra of the film side surface of the metal layer or metal wiring.
[0111] Moreover, the laminate according to the present disclosure preferably has a metal layer or metal wiring, a polymer film according to the present disclosure, and a metal layer or metal wiring, in this order, and more preferably has a copper layer or copper wiring, a polymer film according to the present disclosure, and a copper layer or copper wiring, in this order. Furthermore, the laminate according to the present disclosure preferably comprises, in this order, a polymer film according to the present disclosure, a copper layer or copper wiring, a polymer film according to the present disclosure, a metal layer or metal wiring, and a polymer film according to the present disclosure. The two polymer films according to the present disclosure used in the laminate may be the same or different. The metal layer and metal wiring are not particularly limited and may be any known metal layer and metal wiring. For example, a silver layer, silver wiring, a copper layer or copper wiring is preferable, and a copper layer or copper wiring is more preferable. The metal layer and metal wiring are preferably metal wiring. Furthermore, the metal in the metal layer and metal wiring is preferably silver or copper, and more preferably copper. Since the polymer film according to the present disclosure can be further cured, for example, after attachment of a metal layer or metal wiring, the laminate according to the present disclosure preferably contains a cured product obtained by curing the curable compound A from the viewpoint of durability.
[0112] The method for attaching the polymer film according to the present disclosure to the metal layer or metal wiring is not particularly limited, and any known lamination method can be used.
[0113] The peel strength between the film and the copper layer is preferably 0.5 kN / m or more, more preferably 0.7 kN / m or more, further preferably 0.7 kN / m to 2.0 kN / m, and particularly preferably 0.9 kN / m to 1.5 kN / m.
[0114] In the present disclosure, the peel strength between a film and a metal layer (eg, a copper layer) is measured by the following method. A peel test piece 1.0 cm wide is prepared from the laminate of the film and metal layer, the film is fixed to a flat plate with double-sided adhesive tape, and the strength (kN / m) is measured when the film is peeled from the metal layer at a speed of 50 mm / min using the 180° method in accordance with JIS C 5016 (1994).
[0115] The metal layer is preferably a silver layer or a copper layer, more preferably a copper layer. As the copper layer, a rolled copper foil formed by a rolling method or an electrolytic copper foil formed by an electrolytic method is preferable, and from the viewpoint of flex resistance, a rolled copper foil is more preferable.
[0116] The average thickness of the metal layer, preferably the copper layer, is not particularly limited, but is preferably 2 μm to 20 μm, more preferably 3 μm to 18 μm, and even more preferably 5 μm to 12 μm. The copper foil may be a carrier-attached copper foil formed on a support (carrier) in a peelable manner. As the carrier, a known carrier can be used. The average thickness of the carrier is not particularly limited, but is preferably 10 μm to 100 μm, and more preferably 18 μm to 50 μm.
[0117] The surface roughness Rz of the metal layer or metal wiring on the particle-containing layer side is preferably 1.0 μm or less, more preferably 20 nm to 1,000 nm, and even more preferably 50 nm to 500 nm, from the viewpoint of adhesion between the polymer film and the metal layer or metal wiring.
[0118] In order to further exert the effects of the present disclosure, the metal layer preferably has a group capable of interacting with the film on the surface in contact with the film, and the group capable of interacting with the film is preferably a group corresponding to a functional group of a compound having a functional group contained in the film, such as an amino group and an epoxy group, or a hydroxyl group and an epoxy group. Examples of the group capable of interacting with another molecule include the groups exemplified as functional groups in the compound having the above functional group. Among these, from the viewpoints of adhesion and ease of processing, a group capable of forming a covalent bond is preferred, an amino group or a hydroxy group is more preferred, and an amino group is particularly preferred.
[0119] It is also preferable to process the metal layer in the laminate according to the present disclosure into a desired circuit pattern by, for example, etching, to form a flexible printed circuit board. The etching method is not particularly limited, and any known etching method can be used.
[0120] <Resin layer> From the viewpoint of adhesion between the polymer film and the metal layer or metal wiring, the laminate according to the present disclosure preferably further has a resin layer between the polymer film and the metal layer or metal wiring. The resin contained in the resin layer is not particularly limited, and any known resin can be used. Examples of the resin include thermoplastic resins such as liquid crystal polymers, fluororesins, polymers of compounds having a cyclic aliphatic hydrocarbon group and a group having an ethylenically unsaturated bond, polyether ether ketone, polyolefin, polyamide, polyester, polyphenylene sulfide, polyether ketone, polycarbonate, polyether sulfone, polyphenylene ether and modified products thereof, and polyether imide; elastomers such as copolymers of glycidyl methacrylate and polyethylene; and thermosetting resins such as phenol resins, epoxy resins, polyimide resins, and cyanate resins. Among these, from the viewpoints of the dielectric loss tangent of the film, adhesion to the metal layer or metal wiring, and heat resistance, it is preferable that the film contains a liquid crystal polymer, and it is more preferable that the film contains the resin in the particle-containing layer.
[0121] From the viewpoint of adhesion to a metal foil or metal wiring, the resin layer preferably contains a resin having a group capable of interacting with a metal foil or metal wiring, and the group capable of interacting is preferably a group corresponding to a functional group of a compound having a functional group contained in the film, such as an amino group and an epoxy group, or a hydroxyl group and an epoxy group. The group capable of forming a covalent bond is not particularly limited as long as it is a group capable of forming a covalent bond, and examples thereof include an epoxy group, an oxetanyl group, an isocyanate group, an acid anhydride group, a carbodiimide group, an N-hydroxyester group, a glyoxal group, an imide ester group, a halogenated alkyl group, a thiol group, a hydroxy group, a carboxy group, an amino group, an amide group, an aldehyde group, a sulfonic acid group, etc. Among these, from the viewpoint of adhesion to a metal foil or a metal wiring, at least one functional group selected from the group consisting of an epoxy group, an oxetanyl group, an isocyanate group, an acid anhydride group, a carbodiimide group, an N-hydroxyester group, a glyoxal group, an imide ester group, a halogenated alkyl group, and a thiol group is preferable. When the group present on the surface of the metal foil or metal wiring to be bonded is, for example, a carboxy group, examples of the group capable of covalently bonding with the carboxy group include a hydroxy group and an epoxy group. Furthermore, when the group present on the surface of the metal foil or metal wiring to be bonded is, for example, -NH2 (primary amino group), examples of the group capable of forming a covalent bond with -NH2 include an isocyanate group and an epoxy group. Among these, from the viewpoints of preventing breakage failure during peeling and adhesion, the covalently bondable group is preferably an isocyanate group or an epoxy group, and is particularly preferably an epoxy group. Furthermore, examples of resins having an epoxy group include the jER series manufactured by Mitsubishi Chemical Corporation.
[0122] The content of the resin having a group capable of interacting with a metal foil or metal wiring is not particularly limited, but from the viewpoints of suppressing breakage failure during peeling and adhesion to the metal foil or metal wiring, the content is preferably 0.01 mass % to 10 mass %, more preferably 0.02 mass % to 2 mass %, and particularly preferably 0.05 mass % to 1 mass %, relative to the total mass of the resin layer.
[0123] The resin layer may contain one kind of the above resin alone, or may contain two or more kinds of the above resins. The resin content in the resin layer is not particularly limited, but from the viewpoint of adhesion to the metal foil or metal wiring, it is preferably 50% by mass to 100% by mass, more preferably 80% by mass to 100% by mass, and particularly preferably 90% by mass to 100% by mass, relative to the total mass of the resin layer.
[0124] -Other additives- The films according to the present disclosure may also contain other additives. As the other additives, known additives can be used, specifically, for example, a leveling agent, a defoaming agent, an antioxidant, an ultraviolet absorbing agent, a flame retardant, a colorant, etc.
[0125] From the viewpoints of preventing breakage failure during peeling and adhesion to the metal foil or metal wiring, the average thickness of the resin layer is preferably 10 μm or less, more preferably 5 μm or less, even more preferably 0.5 μm to 5 μm, and particularly preferably 1 μm to 5 μm.
[0126] The method for producing a laminate according to the present disclosure includes a laminate formation step of forming a laminate having a particle-containing layer on a substrate by applying a polymer solution containing at least one resin selected from the group consisting of a liquid crystal polymer, a polysulfone resin, a polyethersulfone resin, and a polyphenylene sulfide resin, liquid crystal polymer particles, and an organic solvent onto the substrate and drying the solution, and a heating step of heating the particle-containing layer at a temperature equal to or higher than the glass transition temperature of the resin, wherein the content of the liquid crystal polymer particles in the particle-containing layer after the heating step is 40% by volume or more. The laminate according to the present disclosure is preferably a laminate produced by the method for producing a laminate according to the present disclosure.
[0127] Preferred aspects of the laminate forming step and heating step in the laminate manufacturing method according to the present disclosure are the same as the preferred aspects of the forming step and heating step in the polymer film manufacturing method according to the present disclosure, except as described below. In addition, in the method for producing a laminate according to the present disclosure, preferred aspects of the layer structure of the obtained laminate and preferred aspects of each layer are the same as the preferred aspects of the layer structure of the laminate according to the present disclosure described above and the preferred aspects of each layer.
[0128] The substrate in the laminate formation step is not particularly limited, but preferably has a metal layer or metal wiring, and more preferably has a metal layer or metal wiring on the surface to which the polymer solution is applied in the laminate formation step. In addition, when metal wiring is used, the base material is preferably a substrate having metal wiring or a resin film having metal wiring. The substrate and the resin film are not particularly limited, and known ones can be used. EXAMPLES
[0129] The present disclosure will be described in more detail below with reference to examples. The materials, amounts used, ratios, processing contents, processing procedures, etc. shown in the following examples can be changed as appropriate without departing from the spirit of the present disclosure. Therefore, the scope of the present disclosure is not limited to the specific examples shown below. In addition, unless otherwise specified, "parts" and "%" are based on mass.
[0130] <Dielectric tangent> The dielectric loss tangent was measured at a frequency of 10 GHz by the resonance perturbation method. A 10 GHz cavity resonator (Kanto Electronics Application Development Co., Ltd. CP531) was connected to a network analyzer (Agilent Technology Corp. "E8363B"), and a film or resin sample (width: 2.0 mm x length: 80 mm) was inserted into the cavity resonator. The dielectric loss tangent of the polymer film or resin was measured from the change in resonance frequency before and after insertion in an environment of 25°C temperature and 60% RH.
[0131] <Breaking elongation> Three test pieces of 10 mm wide and 50 mm long were prepared for each of the polymer film in an arbitrary direction and the direction perpendicular to the arbitrary direction, and the temperature and humidity were controlled for 24 hours at 23°C and 40% relative humidity. Using a Tensilon tensile tester, the 10 mm wide sample pieces were set so that the chuck distance was 30 mm, and a tensile test was performed at a tensile speed of 10 mm / min. The evaluation was performed by measuring three times in each direction and calculating the average value.
[0132] <Preparation of Liquid Crystal Polymer Particles 1> Spherical liquid crystal polymer particles were prepared with reference to Example 1 of WO 2019 / 240153. The median diameter (D50) was 10 μm, the dielectric tangent was 0.0021, and the melting point was 325 ° C.
[0133] <Preparation of Liquid Crystal Polymer Particles 2> Spherical liquid crystal polymer particles were prepared with reference to Example 2 of WO 2019 / 240153. The median diameter (D50) was 40 μm, the dielectric tangent was 0.0021, and the melting point was 325 ° C.
[0134] <Oxidation Treatment of Liquid Crystal Polymer Particles 1 (Preparation of Liquid Crystal Polymer Particles 3)> Liquid crystal polymer particles 1:50 parts were added to NaOH water (NaOH: 40 parts / water: 400 parts) and stirred. Sodium persulfate water (sodium persulfate: 9.6 parts / water: 100 parts) was added, and the temperature was raised to 50°C and stirred for another 3 hours. After cooling to room temperature, the LCP particles were filtered, washed with 500 parts of water, and then thoroughly dried at 40°C to obtain surface-modified liquid crystal polymer particles (liquid crystal polymer particles 3). The median diameter (D50) was 10 μm, the dielectric loss tangent was 0.0021, and the melting point was 325°C.
[0135] <Resin manufacturing> Into a reactor equipped with a stirrer, a torque meter, a nitrogen gas inlet tube, a thermometer, and a reflux condenser, 940.9 g (5.0 mol) of 6-hydroxy-2-naphthoic acid, 377.9 g (2.5 mol) of 4-hydroxyacetaminophen, 415.3 g (2.5 mol) of isophthalic acid, and 867.8 g (8.4 mol) of acetic anhydride were placed, and the gas in the reactor was replaced with nitrogen gas. After that, the mixture was heated from room temperature (23°C) to 140°C over 60 minutes while stirring under a nitrogen gas stream, and refluxed at 140°C for 3 hours. Next, while distilling off by-product acetic acid and unreacted acetic anhydride, the temperature was raised from 150°C to 300°C over 5 hours, and after holding at 300°C for 30 minutes, the contents were removed from the reactor and cooled to room temperature. The obtained solid was pulverized with a pulverizer to obtain a powdered liquid crystal polymer (B1). The flow-initiation temperature of this liquid crystal polymer (B1) was 193°C. The liquid crystal polymer (B1) obtained above was heated from room temperature to 160°C over 2 hours and 20 minutes in a nitrogen atmosphere, then heated from 160°C to 180°C over 3 hours and 20 minutes, and held at 180°C for 5 hours to polymerize in a solid state, then cooled and pulverized in a pulverizer to obtain a powdered liquid crystal polymer (B2). The flow-start temperature of this liquid crystal polymer (B2) was 220°C. The liquid crystal polymer (B2) obtained above was heated in a nitrogen atmosphere from room temperature (23°C) to 180°C over 1 hour 25 minutes, then heated from 180°C to 255°C over 6 hours 40 minutes, and held at 255°C for 5 hours to polymerize in the solid state, and then cooled to obtain a powdered liquid crystal polymer (A). The flow initiation temperature of the liquid crystal polymer (A) was 302°C. The melting point of this liquid crystal polymer (A) was measured using a differential scanning calorimeter, and was found to be 311°C.
[0136] <Preparation of Liquid Crystal Polymer Solution 1> 8 parts of the liquid crystal polymer (A) was added to 92 parts of N-methylpyrrolidone, and the mixture was stirred at 140° C. for 4 hours in a nitrogen atmosphere to obtain a liquid crystal polymer solution 1 (solid content concentration: 8% by mass).
[0137] <Preparation of coating solution> - Preparation of coating solution 1 - The liquid crystal polymer solution 1 (10.0 parts) was mixed with the spherical liquid crystal polymer particles 1 (0.80 parts) to prepare the coating solution 1.
[0138] - Preparation of coating solution 2 - A coating solution 2 was prepared by mixing the liquid crystal polymer solution 1 (10.0 parts) with the spherical liquid crystal polymer particles 1 (1.20 parts).
[0139] - Preparation of coating solution 3 - The liquid crystal polymer solution 1 (10.0 parts) was mixed with the spherical liquid crystal polymer particles 1 (1.87 parts) to prepare a coating solution 3.
[0140] - Preparation of coating solution 4 - The liquid crystal polymer solution 1 (10.0 parts) was mixed with the spherical liquid crystal polymer particles 3 (1.20 parts) to prepare a coating solution 4.
[0141] - Preparation of Coating Solution 5 - The liquid crystal polymer solution 1 (10.0 parts) was mixed with the spherical liquid crystal polymer particles 2 (1.20 parts) to prepare a coating solution 5.
[0142] - Preparation of coating solution 6 - The liquid crystal polymer solution 1 (10.0 parts) was mixed with the spherical liquid crystal polymer particles 1 (0.34 parts) to prepare a coating solution 6.
[0143] <Preparation of undercoat liquid> An aminophenol type epoxy resin ("jER630" manufactured by Mitsubishi Chemical Corporation, 0.04 parts) was mixed with the liquid crystal polymer solution 1 (10.0 parts) to prepare an undercoat liquid.
[0144] Example 1 Using an applicator, the coating solution 1 was applied to a glass plate, and then dried at 50° C. for 3 hours. The cast film was then peeled off from the glass plate and annealed (heated) in a nitrogen atmosphere at 300° C. for 3 hours to produce a polymer film containing 50% by volume of liquid crystal polymer particles 1. The thickness of the polymer film was 25 μm.
[0145] Example 2 The coating solution 2 was applied to a glass plate using an applicator, and then dried at 50° C. for 3 hours. The cast film was then peeled off from the glass plate and annealed at 300° C. for 3 hours in a nitrogen atmosphere to produce a polymer film containing 60 volume % of the liquid crystal polymer particles 1. The thickness of the polymer film was 32 μm.
[0146] Example 3 Using an applicator, the coating solution 3 was applied to a glass plate, and then dried at 50° C. for 3 hours. The cast film was then peeled off from the glass plate and annealed at 300° C. for 3 hours in a nitrogen atmosphere to produce a polymer film containing 75% by volume of the liquid crystal polymer particles 1. The thickness of the polymer film was 48 μm.
[0147] Example 4 The coating solution 4 was applied to a glass plate using an applicator, and then dried at 50° C. for 3 hours. The cast film was then peeled off from the glass plate and annealed at 300° C. for 3 hours in a nitrogen atmosphere to produce a polymer film containing 60 volume % of the surface-modified liquid crystal polymer particles 3. The thickness of the polymer film was 31 μm.
[0148] Example 5 The coating solution 5 was applied to a glass plate using an applicator, and then dried at 50° C. for 3 hours. The cast film was then peeled off from the glass plate and annealed at 300° C. for 3 hours in a nitrogen atmosphere to produce a polymer film containing 60 volume % of the liquid crystal polymer particles 2. The thickness of the polymer film was 34 μm.
[0149] Comparative Example 1 Liquid crystal polymer solution 1 (solid content concentration 8% by mass) was applied to a glass plate using an applicator, and then dried at 50° C. for 3 hours. The cast film was then peeled off from the glass plate and annealed at 300° C. for 3 hours in a nitrogen atmosphere to produce a polymer film that did not contain liquid crystal polymer particles. The thickness of the polymer film was 25 μm.
[0150] Comparative Example 2 The coating solution 6 was applied to a glass plate using an applicator, and then dried at 50° C. for 3 hours. The cast film was then peeled off from the glass plate and annealed at 300° C. for 3 hours in a nitrogen atmosphere to produce a polymer film containing 30 volume % of the liquid crystal polymer particles 1. The thickness of the polymer film was 25 μm.
[0151] <Solubility> 9.0 g of N-methylpyrrolidone was added to 1.0 g of the polymer film of Comparative Example 1, and the mixture was heated and stirred at 140° C. in a nitrogen atmosphere. After heating and stirring for 3 hours, it was confirmed that the mixture was completely dissolved.
[0152] [Table 1]
[0153] As shown in Table 1, the polymer films of Examples 1 to 5 had lower dielectric tangents than the polymer films of Comparative Examples 1 and 2.
[0154] Example 6 A primer liquid was applied to copper foil (product name "CF-T9DA-SV-18", average thickness 18 μm, surface roughness (Rz) 0.6 μm, manufactured by Fukuda Metal Foil and Powder Co., Ltd.), and then heated and dried at 150° C. for 1 hour to form a resin layer of 3 μm on the copper foil. Coating liquid 4 was applied onto the resin layer using an applicator, and then dried at 50° C. for 3 hours. Annealing treatment was performed at 300° C. for 3 hours in a nitrogen atmosphere to produce a laminate having a resin layer and a particle-containing layer containing 60 volume % liquid crystal polymer particles on the metal copper foil. The copper foil was removed from the laminate by etching to obtain a polymer film having a resin layer and a particle-containing layer. The polymer film had a thickness of 35 μm, a dielectric loss tangent of 0.0030, and a breaking elongation of 13%.
Claims
1. The liquid crystal display device has a particle-containing layer containing at least one resin selected from the group consisting of a liquid crystal polymer, a polysulfone resin, a polyethersulfone resin, and a polyphenylene sulfide resin, and liquid crystal polymer particles; The content of the liquid crystal polymer particles in the particle-containing layer is 40% by volume or more, The liquid crystal polymer particles include liquid crystal polymer particles whose surfaces have been subjected to an oxidation treatment. Polymer film.
2. 2. The polymer film according to claim 1, wherein the resin is a liquid crystal polymer.
3. 3. The polymer film according to claim 1, wherein the resin has a solubility in N-methylpyrrolidone at 140° C. of 1% by mass or more.
4. The polymer film according to any one of claims 1 to 3, wherein the resin contains a liquid crystal polymer having a constitutional repeating unit represented by any one of the following formulas (1) to (3): Formula (1) -O-Ar 1 -CO- Formula (2) -CO-Ar 2 -CO- Formula (3) -X-Ar 3 -Y- In formulas (1) to (3), Ar 1 represents a phenylene group, a naphthylene group, or a biphenylylene group; Ar 2 and Ar 3 each independently represents a phenylene group, a naphthylene group, a biphenylylene group, or a group represented by the following formula (4), each of X and Y independently represents an oxygen atom or an imino group, Ar 1 ~Ar 3 Each hydrogen atom in the group represented by the formula: may be independently substituted with a halogen atom, an alkyl group or an aryl group. Formula (4) -Ar 4 -Z-Ar 5 - In formula (4), Ar 4 and Ar 5 each independently represents a phenylene group or a naphthylene group, and Z represents an oxygen atom, a sulfur atom, a carbonyl group, a sulfonyl group, or an alkylene group.
5. 5. The polymer film according to claim 1, wherein the liquid crystal polymer particles have a smaller dielectric tangent than the resin.
6. The polymer film according to any one of claims 1 to 5, wherein the liquid crystal polymer particles have a median diameter of 0.1 µm to 30 µm.
7. A laminate comprising the polymer film according to any one of claims 1 to 6 and a metal layer or metal wiring.
8. The laminate according to claim 7 , further comprising a resin layer between the polymer film and the metal layer or the metal wiring.
9. The laminate according to claim 8 , wherein the resin layer comprises the resin in the particle-containing layer.
10. The laminate according to claim 8 or 9, wherein the resin layer has an average thickness of 5 μm or less.
11. a forming step of forming a particle-containing layer on a substrate by applying a polymer solution containing at least one resin selected from the group consisting of a liquid crystal polymer, a polysulfone resin, a polyethersulfone resin, and a polyphenylene sulfide resin, liquid crystal polymer particles, and an organic solvent onto the substrate and drying the applied solution; a heating step of heating the particle-containing layer at a temperature equal to or higher than the glass transition temperature of the resin, the content of the liquid crystal polymer particles in the particle-containing layer after the heating step is 40% by volume or more; The liquid crystal polymer particles include liquid crystal polymer particles whose surfaces have been subjected to an oxidation treatment. A method for producing a polymer film.
12. a laminate forming step of coating a substrate with a polymer solution containing at least one resin selected from the group consisting of a liquid crystal polymer, a polysulfone resin, a polyethersulfone resin, and a polyphenylene sulfide resin, liquid crystal polymer particles, and an organic solvent, and drying the solution to form a laminate having a particle-containing layer on the substrate; a heating step of heating the particle-containing layer at a temperature equal to or higher than the glass transition temperature of the resin, the content of the liquid crystal polymer particles in the particle-containing layer after the heating step is 40% by volume or more; The liquid crystal polymer particles include liquid crystal polymer particles whose surfaces have been subjected to an oxidation treatment. A method for manufacturing a laminate.
13. The method for producing a laminate according to claim 12 , wherein the substrate has a metal layer or a metal wiring.
14. The method for producing a laminate according to claim 13, wherein the surface roughness Rz of the surface of the metal layer or metal wiring on the particle-containing layer side is 1.0 µm or less.
15. The method for producing a laminate according to any one of claims 12 to 14, further comprising a resin layer between the substrate and the particle-containing layer.
16. The method for producing a laminate according to claim 15 , wherein the resin layer contains the resin in the particle-containing layer.
17. A polymer film comprising at least one resin selected from the group consisting of liquid crystal polymers, polysulfone resins, polyethersulfone resins, and polyphenylene sulfide resins, and a particle-containing layer containing liquid crystal polymer particles, the content of the liquid crystal polymer particles in the particle-containing layer being 40 volume % or more, and a metal layer or metal wiring; A resin layer is further provided between the polymer film and the metal layer or the metal wiring. Laminate.
18. A laminate formation process for forming a laminate having a particle-containing layer on a substrate by applying a polymer solution containing at least one resin selected from the group consisting of a liquid crystal polymer, a polysulfone resin, a polyethersulfone resin, and a polyphenylene sulfide resin, liquid crystal polymer particles, and an organic solvent onto the substrate and drying the applied solution; a heating step of heating the particle-containing layer at a temperature equal to or higher than the glass transition temperature of the resin, the content of the liquid crystal polymer particles in the particle-containing layer after the heating step is 40% by volume or more; The particle-containing layer further includes a resin layer between the substrate and the particle-containing layer. A method for manufacturing a laminate.
Citation Information
Patent Citations
Production of composite resin
JP1989158074A
Surface treatment method of liquid crystal polyester molding and surface treatment apparatus thereof
JP1989216824A
Multiaxially reinforced liquid crystal polymer article
JP1995003124A
Laminate of liquid crystalline polyester with copper foil
JP2007106107A
Biaxially oriented polyarylene sulfide film and method for producing biaxially oriented polyarylene sulfide film
JP2007291222A